PENYALAHGUNAAN SURAT PERNYATAAN PENGUASAAN FISIK DALAM PELAKSANAAN PROGRAM PENDAFTARAN TANAH SISTEMATIS LENGKAP - Muhammad, Yazied Fahma Wijaya; Amiludin, Amiludin (Universitas Muhammadiyah Ponorogo, 2024)
The problem of misuse of the Physical Control Statement Letter (SPPF) in the Complete Systematic Land Registration (PTSL) Program promoted by the government has caused many losses to land rights owners. The writing of this journal is intended to provide education for the public so that they can find out the causes and impacts of misuse of physical possession statement letters (SPPF) in the Complete Systematic Land Registration (PTSL) program, as well as the legal impacts that occur due to misuse of these letters. This journal adopts the Normative Juridical method with an Explorative approach and uses a qualitative analysis technique using primary legal materials, secondary legal materials and tertiary legal materials and the collection technique uses data from literature review. The findings obtained from the results of this study indicate that the misuse of the physical possession letter (SPPF) is due to the vulnerability in the PTSL Law which in this case provides relief for applicants in the Complete Systematic Land Registration (PTSL) program who do not have or do not complete their files as the basis for the right to register the land they own or control can still register their land by using a physical possession statement letter (SPPF). This can have an impact on uncertainty and legal guarantees and can create conflicts over land ownership in the future. In addition, the perpetrators of the misuse of the letter can also face penalties in terms of civil, criminal and administrative matters.